Biodiversity and ecology of the parasitic infracommunities of loricaria prolixa (Siluriformes: Loricariidae) from the Tietê-Batalha Basin, SP, Brazil - Pelegrini, Larissa Sbeghen [UNESP]; Januário, Felipe Freitas; de Azevedo, Rodney Kozlowisky; Abdallah, Vanessa Doro (Universidade Estadual de Maringa, 2018)
The parasitic biodiversity of the Loricaria prolixa, an endemic fish from the Paraná and Prata basins was studied and analyzed the parasitic’s communities dynamics and their ecological relations with this host. Samples were collected in the Batalha River and 39 specimens were analyzed from 2014 to 2016. All fishes were parasitized. The component community was composed by twelve species with 8694 metazoan found on the surface, gills, eyes, brain, intestine and blood of the hosts. Demidospermus spirophallus, Diplostomidae gen. sp., Rhabdochona kidderi and Oligobdella sp. showed higher values for the parasitism's ecological descriptors, and were centrals and dominants species. The infracommunities were characterized by specific richness smaller in relation to diversity, and both superior to equitability (H’ = 0.94; J = 0.6; d = 0.83). There was a significant positive correlation between the host standard length and the parasite abundance of D. spirophallus, Diplostomidae gen. sp. and Oligobdella sp., while Procamallanus (Spirocamallanus) inopinatus presented a significant negative correlation. This is the first contribution concerning the parasite biodiversity of L. prolixa. Clinostomum detruncatum, Diplostomidae gen. sp., Austrodiplostomum compactum, R. kidderi, P. (S.) inopinatus, P. (S.) rebecae, Cucullanus pinnai pinnai, Oligobdella sp. and Trypanosoma sp. were first recorded in this host.
Biodiversidade e ecologia das infracomunidades parasitárias de loricaria prolixa (Siluriformes: loricariidae) provenientes da Bacia do Tietê-Batalha, SP, Brasil
Keywords: Biological diversity; Catfishes; Fish parasites; Freshwater